Historiography of the Post-Restoration Society of Jesus in Spain - Revuelta González, Manuel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The historiography of the Spanish Jesuits in restored Society (1815 -2017) can be divided into the three periods. First period: the bases of scientific historiography, which originate in the last decade of the nineteenth under generalship of Luis Martín and extended during the first three decades of the twentieth century. Second period: historiographical maturity from the 1940s until the 80s. Third period: plurality and specialization in the last two decades of the twentieth century until the present. This article offers the characteristics of the historiography of these periods and the most relevant works and authors, distinguishing between the themes of the old Society and the new, restored one.